2024
DOI: 10.1111/acel.14115
|View full text |Cite
|
Sign up to set email alerts
|

Higher expression of denervation‐responsive genes is negatively associated with muscle volume and performance traits in the study of muscle, mobility, and aging (SOMMA)

Cole J. Lukasiewicz,
Gregory J. Tranah,
Daniel S. Evans
et al.

Abstract: With aging skeletal muscle fibers undergo repeating cycles of denervation and reinnervation. In approximately the 8th decade of life reinnervation no longer keeps pace, resulting in the accumulation of persistently denervated muscle fibers that in turn cause an acceleration of muscle dysfunction. The significance of denervation in important clinical outcomes with aging is poorly studied. The Study of Muscle, Mobility, and Aging (SOMMA) is a large cohort study with the primary objective to assess how aging musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Using the muscle gene expression data, Lukasiewicz et al. ( 2024 ) showed that transcripts that increase with denervation were associated with poorer mobility along with reduced muscle volume.…”
mentioning
confidence: 99%
“…Using the muscle gene expression data, Lukasiewicz et al. ( 2024 ) showed that transcripts that increase with denervation were associated with poorer mobility along with reduced muscle volume.…”
mentioning
confidence: 99%